Using the Appreciative Inquiry Model to Evaluate The Effectiveness of Localized Activity in Teaching Students at Home (LATSH) - P. Ferrer, Nenita; G. Manalo, Nora (International Journal of Management and Education in Human Development, 2024)
The present study improves the performance of Grade 8 students in Technology and Livelihood Education through the Appreciative Inquiry Model to evaluate the effectiveness of Localized Activity in Teaching Students at Home (LATSH). It employed a mixed-method design to understand the research problem better. The paper was divided into four chapters: Discover, Dream, Design, and Deliver. The study respondents were 27% of the total enrolled in Grade 8, belonging to the lower group at Pres. Diosdado P. Macapagal Memorial High School and some TLE teachers. The study administered the pre-evaluation and post-evaluation forms based on Most Essential Learning Competencies (MELCs). The researcher's home-based module (LATSH), which functions as an intervention, was built with extra learning activities, and the results served as the foundation for improving the participants' performance. Administering the home-based learning modules to the TLE students through the pre-test and the summative test revealed a drastic improvement, which means the students are learning step-by-step, which is a good sign. The dream stage consisted of the strengths of the learning modules to facilitate students in optimizing learning. However, it used the implementation of home-based learning for design. It has simplified the teachers' perceptions and views based on related literature. Lastly, in delivering and evaluating the LATSH module in terms of Module Content, Module Teaching and Learning, Module Support, and Module Assessment and Feedback, it was agreed that the module would develop their skills and be a factor for future employment. Based on the study result, the researcher suggested drawing an Action Plan